Influence of Pulse-Like Near-Fault Ground Motions on the Base-Isolated Buildings with LRB Devices - Özuygur, Ali Ruzi; Farsangi, Ehsan Noroozinejad (American Society of Civil Engineers (ASCE), 2021)
Seismic base isolation is a passive structural control system that has been effectively utilized as an innovative seismic-resistant design method in the past decades. The properties of earthquake ground motions have significant effects on the response of the base isolation system. Many recent studies were dedicated to the influence of near-fault ground motions on the response of seismically isolated buildings. These previous studies concluded that near-fault ground motions mostly impose larger displacement on the seismic isolators and, in some cases, larger floor acceleration; furthermore, the velocity pulse period influences the seismic isolator displacement and the floor acceleration. Most of the previous studies were conducted using ground motions simulated with certain parametric conditions of near-fault ground motions and/or a limited number of real earthquake ground motions. This study intended to examine the conclusions of previous studies through response history analysis of a seismically isolated prototype building with lead–rubber bearing (LRB) isolators using a large number of real near-fault earthquake ground accelerations. It was found that no consistent resonance phenomenon can be observed when the velocity pulse period is close to the natural period of the isolated building in terms of floor acceleration and isolator displacement, in contrast to the findings of other studies.